Association of PIK3CA somatic mutations with clinicopathological parameters in breast cancer - Gizem Teoman; Zeynep Turkmen Usta; Zeynep Sagnak Yilmaz; Sevdegul Aydin Mungan; Ismail Saygin (Polish Journal of Pathology)
The enzyme phosphatidylinositide-3-kinase (PI3K) regulates cellular proliferation and apoptosis. Somatic mutations in the PIK3CA gene can accelerate these processes and significantly contribute to the development and progression of breast cancer. This study aimed to ascertain the PIK3CA gene mutations in breast cancer patients and investigate their correlation with certain clinicopathological characteristics. We conducted a mutational investigation of the PIK3CA gene using next-generation sequencing (NGS) in a sample of 100 cases of primary breast cancer. We investigated the associations between PIK3CA mutations and clinicopathological characteristics. Our analysis revealed a mutation rate of 45% in the PIK3CA gene. The mutation frequencies for the three hotspot sites were 33.3% for E545K in exon 10, 26.7% for H1047R in exon 20, and 6.7% for E542K in exon 10. Of the 45 individuals with tumors carrying the PIK3CA mutation, 41 (91.2%) had only one mutation, while 4 (8.8%) had two. Pathogenic PIK3CA mutations were significantly correlated with tumor size ( p = 0.015) and tumor location ( p = 0.017). Our study results demonstrated a significant association between tumor size, location, and presence of the PIK3CA mutation. We must validate these data in larger sample sizes.